Civil economy another idea of the market - Bruni, Luigino 1966-; Zamagni, Stefano 1943- (Agenda, 2023)
This title provides a succinct introduction to the civil economy approach and its history, which draws on the rich Italian tradition of civic humanism and which places well-being, virtue and the common good alongside more familiar economic goals